Priorities And Basic Trends In State Social Policy Aimed At Reducing Poverty In Uzbekistan And The Main Directions Of Expulsion Of Economic Insolvent (Eurasian Journal of History, Geography and Economics, 2023)
In this article, we will mention a number of issues about the fact that several works are being carried out aimed at reducing the poverty of our state, finding its solutions , increasing jobs and eliminating all public and serious problems, a number of works, plans and solutions, on the surface of its manifestations, a large number of taxs and negotiations are being carried out. At the same time , it will not be a lie if we emphasize that this problem is one of the main problems not only of our state, but of the whole world.